Folic acid, vitamin B12, and psychotic symptoms among young psychiatric inpatients - Reis,Filipa Pedro dos (2021)
Abstract Introduction: Folic acid and/or vitamin B12 deficiency are known to be associated with neuropsychiatric disorders. However, the association between serum levels of these molecules and psychotic symptoms is not established. The aim of this study was to investigate the association between folic acid and vitamin B12 serum levels and the presence of psychotic symptoms among child and young adult psychiatric inpatients. Material and Methods: This was a retrospective cohort study of 165 patients under 25 years of age admitted due to psychiatric disorders between 2005 and 2018 and with folic acid and vitamin B12 serum levels assessed during hospitalization. Two groups of patients were defined according to presence or absence of psychotic symptoms. Rehospitalization was also assessed. Results: Folic acid serum levels were significantly lower (p=0.01) in children and young adults hospitalized for psychiatric disorders with psychotic symptoms compared to patients of the same age with acute psychiatric illness without psychotic symptoms. A similar non-significant trend was found for vitamin B12. Rehospitalization rates were also higher in the first group. Conclusion: Results from this study suggest that low folic acid serum levels are associated with psychotic symptoms regardless of the baseline diagnosis.